Performance Sensitivity of NUCA Caches to On-Chip Network Parameters - Bardine, Alessandro; Comparetti, Manuel; Foglia, Pierfrancesco; Gabrielli, Giacomo; Prete, Cosimo A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2008: Anais do XX International Symposium on Computer Architecture and High Performance Computing, 2008)
Non uniform cache architectures (NUCA) are a novel design paradigm for large last-level on-chip caches that has been introduced to deliver low access latencies in wire delay dominated environments. Their structure is partitioned into sub-banks and the resulting access latency is a function of the physical position of the requested data. Typically, to connect the different sub-banks and the cache controller, NUCA caches employ a switched network, made up of links and routers with buffered queues; the characteristics of such switched network may affect the performance of the entire system. This work analyzes how different parameters for the routers, namely cut-through latency and buffering capacity, affect the overall performance of NUCA based systems for the single processor case, assuming a reference organization proposed in literature. The results indicate that the sensitivity of the system to the cut-through latency is very high and that limited buffering capacity is sufficient to achieve a good performance level. As a consequence, we propose an alternative NUCA organization that limits the average number of hops experienced by cache accesses. This organization is better performing in most of the cases and scales better as the cut-through latency increases, thus simplifying the implementation of routers.